Legal Consequences Of Truth Ppat Deed Content, Price Transactions And Date Of Tax Deed After The Enactment Validation In The Boyolali District - Istiningsih Istiningsih; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to identify and analyze: 1) The verification and validation of the contents of the deed tax on PPAT, the price of the transaction and date of the deed PPAT in Boyolali. 2) Obstacles and solutions in the implementation process of verification and validation of tax. 3) The legal consequences of the truth of the PPAT deed, the price of the transaction and date of certificate validation of PPAT following the introduction of the tax in Boyolali.The approach method in this research is juridical empirical research that emphasizes the behavior of individuals or communities in connection with the law. The data used are primary and secondary data obtained through interviews and literature, methods of analysis with descriptive and qualitative analilis.Results of the research results can be concluded: 1) The verification and validation performed Income Tax Office (KPP) Boyolali while BPHTB conducted by the Department of Revenue Management and Asset Finance (DPPKAD) Boyolali. Validation includes the documents and the truth value of the transaction. Clear relation, the transaction value greatly affects the nominal income tax paid to the state. In making the PPAT AJB have to wait for the process validation and manufacturing of Sale and Purchase Agreements can not be specified price and date of the transaction. 2) Barriers due to the use of the transaction value as the basis for calculating BPHTB This has often led to problems in the field, because it is not uncommon transactions submitted by the taxpayer is not considered suitable by the taxman, so it is not uncommon to tax officials in the process of verification / validation, requesting that the transaction value changed and adapted according to the assessment of tax officials. 3) In making the PPAT deed lists the consequences of the transaction price and the date of the deed made and signed. This problem occurs on the inclusion of the transaction price and the date made after the validation is complete, and the parties have been facing the PPAT in early before the validation is performed. Inclusion of the transaction price and date of the deed at the time the parties may face different from the transaction price and the stairs after the validation process. PPAT in this case makes statements that do not fit can be subjected to verbal warning, written, suspension, dismissal with respect and disrespect.Keywords: Transfer of rights; PPAT; Taxes.